MATHEMATICAL MODELLING AND OPTIMIZATION OF HYDROGEN PRODUCTION FROM MICROBIAL ELECTROLYSIS CELL BY USING SOLID WASTE (LEACHATE) - NUR AZMINA, IBRAHIM (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Mathematical modelling and optimization of microbial electrolysis cell (MEC) in production of hydrogen were studied using solid waste leachate. This study introduces a two-phase dynamic model of the MEC in laboratory scale, which was adapted from an existing model constructed on material balances with the integration of bioelectrochemical reactions. The model estimation and validation were executed by estimating the model parameters with experimental results of MEC fed with acetate and simulated landfill leachate, respectively. The maximum hydrogen production achieved in model validation was 0.065 L/day which exceeded the experimental results of MEC fed with simulated landfill leachate by up to 18%. With the positive results from model validation, the model was optimized to minimize the gap between simulated and experimental results of MEC fed with leachate. After the optimization approach, the mean average of deviations was reduced by 63.6% as compared to deviations before optimization. Thus, maximum hydrogen production was obtained at 0.06 L/day. The optimized model was used to study and examine the performances of microbial and hydrogen production rate throughout the MEC operation with simulated landfill leachate. This model is capable of illustrating the behaviour of anodophilic, acetoclastic methanogenic and hydrogenotrophic microorganisms with their growth and metabolic activities during the 15 days. This model also able to simulate hydrogen production in the MEC fed with simulated landfill leachate. The highest peak of hydrogen formation rate obtained in this study was 0.0604 L/day.